2019
DOI: 10.1186/s12879-019-4314-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the annual risk of infection with Mycobacterium tuberculosis among adolescents in Western Kenya in preparation for TB vaccine trials

Abstract: Background Adolescents are a prime target group for tuberculosis (TB) vaccine trials that include prevention of infection (POI). The BCG vaccine is given at birth and does not prevent TB infection. TB infection, a critical endpoint for POI vaccine trials would need to be documented to estimate sample sizes in target populations. Methods Adolescents aged 12–18 years of age were enrolled in an area under continuous demographic surveillance. A tuberculin skin test (TST) su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Among eligible Tanzanian adolescents followed for up to 3 years the annual rate of incident positives was 2.9%. That rate is comparable to the 2.6% (95% CI 2.2-3.1) rate reported among adolescents in Kenya [20], but lower than the 4% to 14% rates reported in South Africa [7,21]. With only a single IGRA-assay we cannot determine with certainty how many of the prevalent positives in our trial represent persistent positives.…”
Section: Plos Onecontrasting
confidence: 51%
“…Among eligible Tanzanian adolescents followed for up to 3 years the annual rate of incident positives was 2.9%. That rate is comparable to the 2.6% (95% CI 2.2-3.1) rate reported among adolescents in Kenya [20], but lower than the 4% to 14% rates reported in South Africa [7,21]. With only a single IGRA-assay we cannot determine with certainty how many of the prevalent positives in our trial represent persistent positives.…”
Section: Plos Onecontrasting
confidence: 51%
“…These findings are similar to those reported in the age and sex model study done in Zambian and South African communities [ 28 ] and by Nduba V. et al . in western Kenya [ 29 ]. Our findings, plus those reported elsewhere [ 10 – 13 , 30 , 31 ], indicate that M .…”
Section: Discussionmentioning
confidence: 99%
“…A large case-control study of AYA at boarding schools in China found that index students had a history of significant household exposure but not prior classroom exposure [91]. Community surveillance studies in Uganda and Kenya also identified a higher prevalence of TB infection among AYA who had left school compared with school-going AYA, though only a small proportion of AYA in each study had left school [69,[92][93][94].…”
Section: School Exposuresmentioning
confidence: 97%